Electroreduction of CO2 to Formic Acid with Pb-Sn Alloy Cathode - Hudoyo, Henry
The increase of world population has caused a step-up on industry activity and fossil fuel’s use on earth. The usage of fossil fuel will increase greenhouse effect, where this phenomenon is usually called global warming. From that fact, greenhouse gases especially CO2 must be reduced in order to minimalize global warming. Many technologies have been developed to reduce CO2 level on air. However, these technologies still focused on how CO2 is caught and saved. It hasn’t considered how CO2 is converted to another product. Hence, electrochemistry reduction of CO2 which can convert CO2 to another compound having a high economic value, should be developed. In this experiment, formic acid is chosen as the primary product since it has many functions on daily life. This CO2 electrochemistry reduction is carried out with Pb-Sn cathode, Pt-Ir anode, and 0.1 M H2SO4 as anolyte. CO2 was bubbled to be dissolved in a 400 mL catolyte with a bubbling flow rate of 75 mL/minute. Electricity is given by DC power supply, where catolyte type, concentration, and voltage were varied in this experiment. The final product of formic acid has been analyzed using high performance liquid chromatography. Based on the experiment, it can be concluded that KHCO3 electrolyte gives higher amount of formic acid product and higher faradaic efficiency. Electrolyte concentration and cell voltage in the range of 0.1-1 V are directly proportional to product amount and faradaic efficiency. The optimum amount of formic acid that can be produced from this experiment is 9400 ?mol, by using 0.5 M KHCO3 catholyte and 1 V overpotential. This variation has provided a faradaic efficiency of 67.19% and conversion of 0.326%.